Hubungan Antara Iklan Shopee di Televisi dan Daya Tarik Brand Ambassador Shopee Terhadap Minat Unduh Aplikasi Shopee - Petrus Orseola Rosarianto; Djoko Setyabudi (Interaksi Online, 2021)
This study aims to determine the relationship between Shopee television ads exposure and Shopee brand ambassador attractiveness with download interest of Shopee application. It is hoped that the implementation of this research will be beneficial for the development of communication study both theoretically and practically. This study will use elaboration likelihood model theory and cognitive communication theory to examine relationship between advertisement exposure and brand ambassador to the shopee application download interest. As practical matter, it is hoped that this research can be a suggestion in preparing a marketing communication plans for e-commerce. For further research, researcher suggest examining using integrated marketing approach to find out the most effective marketing communication strategies in this digital age.